INFLUENCE OF FLUORIDE ON DENTAL TISSUES: MINI-REVIEW AND OWN RESEARCH - Kostyrenko, Oleksij P.; Nikolishin, Anatoly K.; Kotelevska, Natalya V.; Nikolishyna, Ella V.; Ilenko, Nataliya M.; Маrchenko Аlla V. (Eastern Ukrainian Medical Journal, 2026)
Dental fluorosis is a general medical problem, common in many countries of the world. The clinical signs of fluorosis are localized in the maxillofacial area and are of great importance for the quality of life of patients (aesthetics, impaired chewing function, etc.). People are exposed to fluorides not only through food and water, but also from industrial and pharmaceutical products. Fluoride compounds are also used in dentistry to prevent dental caries. Excessive consumption of fluoride-containing products in children can lead to poisoning or fluorosis. According to WHO, the problem of dental fluorosis remains relevant. Research objective: to characterize the structural changes in teeth enamel with different manifestations of fluorosis. Materials and methods: the study was conducted on the basis of Poltava State Medical University (Ukraine). Сontent of fluoride in the drinking water of Karliv’s and Mashiv’s districts of Poltava region is 7–12 mg/l. Dental fluorosis was diagnosed in 58 patients of 25–44 years. For orthodontic and surgical indications, 18 fluorotic and intact teeth were removed. With the help of scanning electronic microscopy, the enamel surface structure was studied, and penetration of ammonia silver into enamel and dentin was assessed using light microscopy. Results and discussion: according to the results of scanning electron microscopy, in mild and moderate cases, an inhomogeneous structure of the enamel is determined, the density of prisms in the rows is disturbed. In severe fluorosis, deep deformations and significant destruction of the enamel prisms occur. After impregnation with a solution of ammonia silver in intact teeth, a strip of uniform accumulation of the dye was observed in the surface layer of the enamel along the entire perimeter of the crown. In moderate fluorosis, the dye penetrated into the surface and deep layers of the enamel, and in severe fluorosis, into the deep layers of the enamel and beyond the enamel-dentine boundary. Enamel damage is localized on the vestibular and oral surfaces of the tooth. Histological examination confirmed that fluorinated enamel has a porous structure. This leads to rapid pigmentation of the surface layer of the enamel due to the diffusion of exogenous dyes. Conclusions: the microstructure and chemical composition of hard tooth tissues reflect processes associated with the pathology of teeth and the whole organism. Structural changes in tooth enamel with various manifestations of fluorosis indicate a violation of the architectonics of enamel prisms and interprismatic substance.